Simultaneous Occurrence of Herpes Zoster and Chickenpox in a Patient - A Case Report (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Varicella zoster virus (VZV) infection primarily causes varicella or chickenpox. Herpes zoster (HZ) or shingles is themanifestation due to reactivation of same virus. Simultaneous occurrence of HZ and Chickenpox in a patient is anuncommon event. A 14 years old apparently healthy girl came to the medicine outpatient department of PirojpurDistrict Hospital with the complaints of burning pain in the right side of forehead followed by maculopapular rashand blister lesion with painful right red eye. The lesions were anatomically distributed along the dermatome of rightsided ophthalmic division of trigeminal nerve. Simultaneously she developed some small vesicular lesion in hertrunk. At that time she had fever, bodyache and malaise. The entire lesion was healed with crusting within seven toten days. She had no significant past history. With a course of antiviral and symptomatic treatment, she recoveredwithout any complication.Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(1):03-07